2014
DOI: 10.1371/journal.pone.0105189
|View full text |Cite
|
Sign up to set email alerts
|

Protection Patterns in Duck and Chicken after Homo- or Hetero-Subtypic Reinfections with H5 and H7 Low Pathogenicity Avian Influenza Viruses: A Comparative Study

Abstract: Avian influenza viruses are circulating continuously in ducks, inducing a mostly asymptomatic infection, while chickens are accidental hosts highly susceptible to respiratory disease. This discrepancy might be due to a different host response to the virus between these two bird species and in particular to a different susceptibility to reinfection. In an attempt to address this question, we analyzed, in ducks and in chickens, the viral load in infected tissues and the humoral immune response after experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
3
16
1
Order By: Relevance
“…Previously, in other aquatic bird species, LPAIV infection induced partial protection against subsequent infection with a homologous virus and partial to nearly complete protection against subsequent infection with a heterologous virus. Similar to our findings in BHGU, LPAIV infection also induced partial protection against reinfection with the homologous virus in mallards (H7N7) (8) and Pekin ducks (H5N3 and H7N2, respectively) (7,18). In those studies, the time interval between the first and second inoculations was relatively short, ranging from 21 to 84 days.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previously, in other aquatic bird species, LPAIV infection induced partial protection against subsequent infection with a homologous virus and partial to nearly complete protection against subsequent infection with a heterologous virus. Similar to our findings in BHGU, LPAIV infection also induced partial protection against reinfection with the homologous virus in mallards (H7N7) (8) and Pekin ducks (H5N3 and H7N2, respectively) (7,18). In those studies, the time interval between the first and second inoculations was relatively short, ranging from 21 to 84 days.…”
Section: Discussionsupporting
confidence: 89%
“…The following differences in study design may play a role in this discrepancy. Compared to our study, the LPAIV subtypes used in those studies were different (H5N3 and H7N2 [7], H7N7 and H5N2 [8], and H3N8 and H5N2 [9]); the time interval between the first and second inoculations, 14 (8) or 21 days (7, 9), was shorter; the inoculum dose, 4 ϫ 10 6 PFU (7) or 10 8.7 EID 50 (8), was higher; and there were two prior infections with a heterologous virus (8) rather than one. In free-living mallards, heterosubtypic LPAIV immunity has been described for different HA subtypes belonging to the same phylogenetic clade (19).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Because protective immunity acts more effectively within than between HA groups, we chose viruses from HA clade 1 (the clade that includes H5 viruses). Within this clade, we chose HA types that had been experimentally associated with reducing the severity of subsequent HPAI H5N1 infections (H5 and H9 [31,34,45,46]) or were antigenically close to H5 viruses (H6). H6 viruses were among the most common viruses in European waterfowl around the sampling period of 2007/2008, particularly in geese and swans [28,47,48].…”
Section: Methodsmentioning
confidence: 99%
“…Although the H4 and H6 subtypes were also frequent in surveillance studies in Europe, recurrent detection of other subtypes was not significantly different [5, 13]. Seasonal patterns of IAV prevalence among wild birds have been described; however, factors and mechanisms that drive diversity and prevalence of IAV subtypes such as the effects of homo- and heterosubtypic immunity remain unclear [14, 15]. Previous studies have demonstrated the induction of homosubtypic and partial heterosubtypic immunity in mallards [1620], and this has been supported further by field observations [21].…”
Section: Introductionmentioning
confidence: 99%